The global journey of an Asian : the entrepreneurial journey of a complete outsider - Palan, R., (Advantage Media, 2013)
A story of hope, courage, and determination and learning the lessons of entrepreneurial life. Dr. Palan explores the lessons and gifts of his extraordinary entrepreneurial journey. Based on personal experiences and examples from business and politics, this book is about defining your own success, knowing where you want to go but also being flexible and allowing life to take you in unexpected directions, connecting passion to purpose, truly understanding yourself and your strengths, being resilient, and the importance of continuing to learn.